Strategi Pengumpulan Dana Zakat Pada Badan Amil Zakat Nasional (BAZNAS) Kota Padang - Rinaldi, Rizki Alif; Asmadia, Tezi (IAIN Batusangkar, 2024)
The main problem in this research is the strategy for collecting zakat funds at the Padang City National Zakat Amil Agency (BAZNAS). The aim of the research is to explain and describe the strategy for collecting zakat funds at the Zakat Amil Agency at the National Zakat Amil Agency BAZNAS Padang City.The type of research that researchers use is (field research) field research with qualitative descriptive methods. The data collection technique that the author carried out was interviews with the leadership, deputy chairman I, chief executive, head of collection and BAZNAS collection staff in Padang City and documentation in the form of pamphlets, brochures supporting zakat collection. Data analysis techniques are data reduction, data presentation, and drawing conclusions. The research results reveal that the strategy for collecting zakat funds at BAZNAS Padang City uses two methods, namely a direct strategy and an indirect strategy. Researchers also found unique things in zakat fund collection strategies, such as digitalization of zakat collection, education and outreach programs, collaboration with companies and community leaders, special events, zakat product innovation, integrated services, and reward programs. Then the supporting factors are competent amil, government support, innovation and technology, social religious activities, partnership networks, media and communication, while the inhibiting factors are the lack of public awareness of giving zakat through BAZNAS Padang City.